Mobilizing management knowledge in healthcare: Institutional imperatives and professional and organizational mediating effects. Issue 5 (November 2017) - Bresnen, Mike; Hodgson, Damian; Bailey, Simon; Hyde, Paula; Hassard, John
Recent changes within UK healthcare have had dramatic consequences for management and put managerial capabilities firmly under the spotlight. Yet, despite extensive research on managers, comparatively little is known about how they acquire and apply their management knowledge and how this is influenced by their professional background and organizational context. Drawing upon work that distinguishes between different forms of knowledge, managers' mobilization of management knowledge is examined in the light of recent changes in healthcare. Case study evidence is presented from diverse managerial groups across three types of hospital trust (acute, care and specialist). The analysis demonstrates the mediating effects of interactions between professional background and organizational context on knowledge mobilization and highlights how current pressures on public services are reinforcing a reliance on existing management practices, creating enormous challenges for management learning in this sector.